Study on the knowledge dissemination efficiency and influence factors of electronic technology journals community based on the DEA-Tobit method. Issue 4 (April 2020) - Peng, Huiling; Qu, Hui; Li, Ping
Abstract: [Research objective] The construction of the journal community as the key content of the development of electronic technology, is of great practical significance to research knowledge production and dissemination efficiency of the journal community.[Research methods and data sources] This paper, by using DEA-Tobit model and in combination with the Chinese S&T Journal Citation Reports (Expanded Edition), focuses on the evaluation of the knowledge dissemination efficiency of electronic technology journal communities from the perspective of knowledge exchange, and demonstrates and studies the factors that affect the knowledge dissemination efficiency of journal communities.[Conclusion](1) Generally speaking, there is still 31% optimization space for the knowledge dissemination performance of the electronic technology journal community, and the low scale efficiency value has a large impact on it. (2) Journals such as Electronic Products, Light & Lighting, Journal of University of Electronic Science and Technology of China, and Journal of Chinese Electron Microscopy Society have relatively high knowledge transmission efficiency, and the value of technical efficiency, pure technical efficiency, and scale efficiency of those journals are equal to 1. (3) The academic quality of journal papers is the key variable to influence the electronic technical journal community knowledge dissemination efficiency; the duration of the journal and the economic status of the journal location are also positive factors affecting the effectiveness of journal knowledge dissemination; factors such as the degree of journal cooperation, the internationalization level of journals, and the institutional distribution of journal articles have a limited impact on the effectiveness of knowledge dissemination in the journal community. In addition, in view of the lower time-sensitive of the electronic technology literature, the overall influence of the novelty of the literature used by authors, which is measured by "cited half-life", on the performance of knowledge exchange is quite different from expectations.